Diarrhoea and acute respiratory infections prevalence and risk factors among under-five children in Iraq in 2000 - Siziya Seter (Italian Journal of Pediatrics, 2009)
Abstract Background Diarrhoea and acute respiratory conditions are common medical conditions among under-five children in resource-limited and conflict situations. The present study was conducted to estimate the prevalence and associated factors for acute respiratory conditions and diarrhoea among children under the age of five years in Iraq in 2000. Methods Data for the Iraqi Multiple Indicator Cluster Survey were obtained from UNICEF. We estimated the prevalence of acute respiratory conditions and diarrhoea. Assessment of the associations between these two medical conditions on one hand and socio-demographic and environmental variables on the other was done using logistic regression analysis. Weighted analysis was conducted to account for complex survey design. Results A total of 14,676 children under the age of 5 years were reported by their mothers in the study. Of these 50.4% were males. About half (53.9%) of the children had complete vaccination status. Overall, 21.3% of the children had diarrhoea, and 6.9% had acute respiratory infection (ARI) in the last two weeks. In multivariate analysis, diarrhoea was associated with age of child, area of residence, maternal education, source of water, toilet facility, disposal of children' stool and disposal of dirty water. Compared to children aged 48–59 months, children in the age groups 6–11 months and 12–23 months were 2.22 (95%CI [2.02, 2.44]) and 1.84 (95%CI [1.71, 2.00]) times more likely, respectively, to have diarrhoea. Children whose mothers had no formal education were 11% (AOR = 1.11, 95%CI [1.04, 1.18]) more likely to have diarrhoea compared to children with mothers who had attained secondary level of education. Compared to children who belonged to households with unprotected well or river as the main source of water, children who belonged to households with piped water were 32% (AOR = 1.32, 95%CI [1.17, 1.48]) more likely to have diarrhoea while those who belonged to households with protected well were 26% (AOR = 0.74, 95%CI [0.62, 0.89]) less likely to have diarrhoea. Age of child, toilet facility, wealth, and sex of child were significantly associated with ARI. Conclusion In a study of under-five children in Iraq in 2000, we found that history of diarrhoea and ARI were negatively associated with lower socio-economic status, adequate disposal of children's stool and dirty water, but the results were inconsistent in terms of access to potable water and sanitation facilities possibly due to non-functioning of water and sewage plants after the war. Improvement in water quality and sanitation are vital in the reduction of diarrhoeal diseases.